Rapid degeneration of rod photoreceptors expressing self-association-deficient arrestin-1 mutant - Song, Xiufeng (2013)
Arrestin-1 binds light-activated phosphorhodopsin and ensures timely signal shutoff. We show that high transgenic expression of an arrestin-1 mutant with enhanced rhodopsin binding and impaired oligomerization causes apoptotic rod death in mice. Dark rearing does not prevent mutant-induced cell death, ruling out the role of arrestin complexes with light-activated rhodopsin. Similar expression of WT arrestin-1 that robustly oligomerizes, which leads to only modest increase in the monomer concentration, does not affect rod survival. Moreover, WT arrestin-1 co-expressed with the mutant delays retinal degeneration. Thus, arrestin-1 mutant directly affects cell survival via binding partner(s) other than light-activated rhodopsin. Due to impaired self-association of the mutant its high expression dramatically increases the concentration of the monomer. The data suggest that monomeric arrestin-1 is cytotoxic and WT arrestin-1 protects rods by forming mixed oligomers with the mutant and/or competing with it for the binding to non-receptor partners. Thus, arrestin-1 self-association likely serves to keep low concentration of the toxic monomer. The reduction of the concentration of harmful monomer is an earlier unappreciated biological function of protein oligomerization.